Analysis of birth weight data from the Malaysian family life survey II - Bulgiba, Awang; Sallam, A.A. (SAGE Publications, 1999)
An analysis of birth weight was undertaken on secondary data derived from the Malaysian Family Life Survey II. A total of 1629 last singleton live birth infants was analysed with the aim of identifying from the variables available potential risk factors for low birth weight. Univariate and subsequently multivariate analyses were carried out for this purpose. The incidence of low birth weight was 11.8 percent. Race, parity and prematurity were found to be significantly associated with low birth weight after controlling of the other variables. The findings indicate that more work needs to be done to establish the underlying reasons for low birth weight in Malaysia.